Digital Census And Sustainable Development: Evaluating The Accuracy And Reliability Of Digital Census Data - Younus, Muhammad; Zuly Qodir (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2023)
This study looks at the quality and dependability of digital census data in the context of sustainable development. The study compares digital census approaches traditional paper-based systems using a mixed-methods approach, concentrating on data quality, accessibility, and their contribution to sustainable development goals. The results show that digital census data is more accurate and reliable than traditional techniques, with fewer errors and inconsistencies. Furthermore, digital data is more accessible and easier to evaluate, allowing for better-informed decision-making for long-term development. However, obstacles such as the digital gap and privacy concerns must be solved for digital census methodologies to be implemented successfully. This paper demonstrates how digital census data may greatly help sustainable development by providing accurate, reliable, and easily accessible information. Digital census methodologies can be essential in designing a sustainable future by solving recognized hurdles and exploiting digital technology benefits.